2020
DOI: 10.17582/journal.sja/2020/36.3.966.973
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Maize Production in Central Khyber Pakhtunkhwa, Pakistan

Abstract: M aize (Zea mays L.), a member of grass family (Gramineae) originated in Central America, is used by human civilization even in the ancient times. Maize is a C4 plant, having high genetic potency and is a photosynthesis explorative crop. Maize grain contains about 79% starch, 10% protein, 4% fiber, 4%fat and 3% minerals (Ahmad et al., 2017). It is mostly grown for grain as well as for fodder purposes and is also used as a raw material by various manufacturing units like cooking oil, confectionary and backers.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…That is the reason deeply tilled land is always preferred over conventional and conservative tillage in rice farming because the former situation results more yield as compared to the later one (Arora et al, 2018). In the current study the rice farmers did so and the estimated coefficient of tractor hours (0.04) was positive and highly significant at 5% level of significance, implying that rice yield significantly increased by 0.04% with respect to a unit change in the use of tractor and the results are in line to that of Shah et al (2020) while estimating determinants of rice crop.…”
Section: Estimates Of Cobb-douglas Type Production Functionsupporting
confidence: 81%
See 1 more Smart Citation
“…That is the reason deeply tilled land is always preferred over conventional and conservative tillage in rice farming because the former situation results more yield as compared to the later one (Arora et al, 2018). In the current study the rice farmers did so and the estimated coefficient of tractor hours (0.04) was positive and highly significant at 5% level of significance, implying that rice yield significantly increased by 0.04% with respect to a unit change in the use of tractor and the results are in line to that of Shah et al (2020) while estimating determinants of rice crop.…”
Section: Estimates Of Cobb-douglas Type Production Functionsupporting
confidence: 81%
“…In the last stage, a total of 275 respondents from four union councils were picked randomly. Yamane's formula was used to decide the size of the sample for this study as it is used generally (Yamane, 1967;Ahmad et al, 2019;Murtaza et al, 2020), given as;…”
Section: Study Locationmentioning
confidence: 99%
“…Te mean family size of the household head in a single dwelling was 5.55, with a minimum of one and a maximum of ten. Tis fnding is supported by Shah et al [21] and Belayneh et al [20] who reported larger family sizes, implying that it was above the average household size of the national 4.70. It emphasized the relevance of larger families participating in agricultural production, especially when all household members contribute to the family's economy through increased productivity and the provision of services [22].…”
Section: Socioeconomic Characteristics Of the Respondentsmentioning
confidence: 82%
“…Demographic characteristics such as farming experience, age, education level, tenancy status and primary source of income influence the inefficiency of farming community in a production process (Murtaza et al, 2020). The statistics showed that rice growers in the study area had an average age of 45.5 years, with the maximum, minimum and std.…”
Section: Summary Statistics Of Variables Used In Sfm-1mentioning
confidence: 95%
“…and Aigner et al (1977) both the terms are independent of each other and "ui" shows the technical inefficiency of an individual or simply it captures the gap in observed output to that of the frontier level output, half normally distributed and always greater than 0 (ui>0) while "vi" term of the composed error indicates the random factors that are far beyond someone's control (luck, climate, and other natural calamities) and is normally distributed on both the sides (-∞<vi<∞). Because of the consistency and specialty of the stochastic frontier production approach, the study implied this model to analyze the farmers' efficiency and inefficiency (technical) followingMurtaza et al (2020),Ali et al (2019),Khai and Mitsuyasu (2011), Coelli et al (2005),Kebede (2001), Bravo-Ureta et al (1991,Belbase and Grabowski …”
mentioning
confidence: 99%